THE ROLE OF SUPPORT NETWORKS IN THE ADOPTION OF SUSTAINABLE AGRICULTURE: A LITERATURE REVIEW - Mohd Firdaus Ruslan; Haliyana Khalid (International Journal of Accounting, Finance and Business, 2023)
This paper reviews the limited knowledge and information regarding sustainable agriculture among farmers and the potential role of social networks in addressing this issue. Promoting sustainable agriculture is challenging, and farmers may lack the necessary knowledge and resources to adopt sustainable practices. To address this, enhancing social networks can be a crucial strategy to improve access to information and knowledge related to sustainable agriculture. The review draws on 25 articles published in the Web of Science (WOS) database between 2014 and 2023, where the result indicates a growing interest in this area with increasing number of publications. The review suggests that social networks can be categorised as either formal or informal, each playing a distinct role in supporting sustainable agriculture. Formal social networks such as extension agent services and farmers’ associations can provide farmers with valuable information and resources, helping bridge the gap between knowledge and practice. In particular, informal social networks such as farmer-to-farmer and neighbour support networks can play a vital role in facilitating knowledge sharing and adopting sustainable practices. These networks are built on trust and mutual respect and can provide farmers with practical advice and guidance on improving their farming practices. Additionally, the paper recommends improving extension agent services and strengthening farmers' associations to enhance the adoption of sustainable agricultural practices. In conclusion, enhancing social networks can be a critical strategy in promoting sustainable agriculture, particularly in rural areas where farmers may lack access to information and resources. By strengthening informal and formal social networks, farmers can gain the knowledge, skills, and resources they need to adopt sustainable practices, ultimately leading to a more sustainable agricultural sector.